Rancang Bangun Alat Bantu Cek Spool Valve di PT. Mulia Indo Consolidated Menggunakan Sistem Offliner - Nugroho, Oktavianus Ardhian (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2024)
There are various kinds of industries in Indonesia, one form of industry is the type of F&B Industry (food and beverage). PT. MIC (Mulia Indo Consolidated) is one of the industries engaged in F&B which is oriented towards the production of bottles and packaging. The machines in PT. MIC uses a part that functions to regulate fluid flow in a hydraulic or peumatic system, this part is often referred to as a spool valve. At PT. MIC spool valve is used to move the mold, compress air and move other parts that support the bottle forming process. At PT. MIC components of this spool valve must be maintained so that it can work properly, so far the checking process is done manually by checking the performance of the spool valve at a pressure of 20 Psi or about 138 newtons per square meter this value is equated with the pressure conditions when this spool valve works in making bottles. At PT. MIC components of this spool valve must be maintained so that it can work properly, so far the checking process is done manually by checking the performance of the spool valve at a pressure of 20 Psi or about 138 newtons per square meter this value is equated with the pressure conditions when this spool valve works in making bottles. From the manual testing process of the spool valve, you can get the condition of the spool valve that is still good or not, but the weakness is because the manual process is still low and the process is long. Therefore PT. MIC and the ATMI Industrial Polytechnic (Polin ATMI) work together to make a spool valve test equipment that aims to find out whether the repaired spool valve is in accordance with the standard pressure value of 20 Psi so as to minimize repeated breakdowns. The spool valve check tool is made using an offliner system so that it does not interfere with the machine when producing. From the results of this study, a spool valve check device was successfully designed and made to work well when carrying out the spool valve inspection process so as to reduce the repeated breakdown process and increase production.